2018
DOI: 10.1055/s-0038-1667320
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Endoscopy Intervention in Postesophagectomy Anastomotic Leak: A Retrospective Study

Abstract: Endoscopy intervention is safe and effective in the diagnosis and treatment of postesophagectomy anastomotic leak. Especially for patients with a diameter of anastomotic leaks greater than 5 mm, the advantages of endoscopy intervention should not be neglected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…6) [22,33,48]. There was a significantly shorter ICU length of stay in the EVT group compared to the stent group Weighted mean (95% CI) I 2 , % Hospital length of stay, days Endoscopic treatment 45.9 (35.9-55.9) [22, 26, 30, 33, 35, 39-41, 43, 44, 46, 48, 51] 97 EVT 51.4 (45.1-57.7) [22,33,44,46,48] 32 Stent placement 44.6 (31.8-57.4) [22,26,30,33,40,41,43,48,51] 97 Surgical treatment 41.9 (30.9-52.9) [39,47,48,51] 72 ICU length of stay, days Endoscopic treatment 19.5 (13.0-26.0) [22,48,50] 69 EVT 18.1 (3.8-32.5) [22,48] 87 Stent placement 21.1 (12.7-29.5) [22,48,50] 41 Surgical treatment 21.7 (3.4-40.1) [47,48] 86…”
Section: Evt Versus Stentmentioning
confidence: 99%
See 1 more Smart Citation
“…6) [22,33,48]. There was a significantly shorter ICU length of stay in the EVT group compared to the stent group Weighted mean (95% CI) I 2 , % Hospital length of stay, days Endoscopic treatment 45.9 (35.9-55.9) [22, 26, 30, 33, 35, 39-41, 43, 44, 46, 48, 51] 97 EVT 51.4 (45.1-57.7) [22,33,44,46,48] 32 Stent placement 44.6 (31.8-57.4) [22,26,30,33,40,41,43,48,51] 97 Surgical treatment 41.9 (30.9-52.9) [39,47,48,51] 72 ICU length of stay, days Endoscopic treatment 19.5 (13.0-26.0) [22,48,50] 69 EVT 18.1 (3.8-32.5) [22,48] 87 Stent placement 21.1 (12.7-29.5) [22,48,50] 41 Surgical treatment 21.7 (3.4-40.1) [47,48] 86…”
Section: Evt Versus Stentmentioning
confidence: 99%
“…Sensitivity analysis excluding an outlier (Freeman et al [30], 12 days until AL resolution after stent placement) did not significantly affect the estimates. Mean time until oral intake, only reported in 4 stent studies, ranged between 1.7 and 28.8 days [25,36,40,43]. Double-Arm Meta-Analysis Meta-analysis of the studies directly comparing EVT with stent placement revealed that EVT was associated with nonsignificantly higher clinical success (OR 1.91 [95% CI: 0.47-7.79]) [22,33], lower in-hospital mortality (OR 0.39 [95% CI: 0.13-1.18]) [22,48], and lower endoscopic (OR 0.21 [95% CI: 0.02-1.88]) (online suppl.…”
Section: Evt Versus Stentmentioning
confidence: 99%
“…Therefore, diagnosis should be early and multidisciplinary (11,14,33). Currently, early diagnosis and advanced non-surgical therapy have led to a paradigm shift in the treatment of AL, from aggressive surgical intervention to non-surgical management (3,7,33,34). Because the mortality rate of re-operations is up to 60%, most surgeons prefer nonsurgical treatment (31).…”
Section: Early Recognition and Diagnosismentioning
confidence: 99%
“…Anastomotic leakage (AL) is one of the most critical and detrimental complications in esophageal surgery (2,3). The incidence of AL is about 10%, is often unpredictable in nature, and varies widely among institutions and surgeons, with a significantly higher incidence of cervical AL of 10% to 20% compared with intrathoracic AL (5)(6)(7)(8). Given the high incidence and morbidity of AL, identification of the causes and precipitating factors, techniques for prevention, early diagnosis, and management strategies is critical (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…A conservative approach is sometimes insufficient and surgery may be hindered due to tissue fibrosis and local inflammation. Use of endoscopy in this scenario is being explored, as an alternative to lessen hospital stay, medical expenditure, days of limited oral intake and postoperative complications, particularly in patients with fistulas larger than 5 mm [2]. Many endoscopic approaches are emerging, but there is still a lack of consistency in the literature about which is the best, meaning that none has achieved clearly superior results regarding leak resolution and complications.…”
mentioning
confidence: 99%